The production of monacolin K, citrinin and pigments in noodle waste nngkak fermented by various monascusstrains - Chattong, Utaiwan; Dajanta, Katekan (Asia-Pacific Journal of Science and Technology, 2017)
This study aims to investigate the production of monacolin K, citrinin and pigments in noodle waste angkak fermented by 4 strains of Monascusincluding Monascussp. PSRU03, M. purpureusATCC16365, M. purpureus BCC6131 and M. ruberTISTR3006. The results found that angkak samples from 4 strains of Monascuscontained pigments of 95.65 – 293.87 unit/g DM, monacolin K contents of 8.05-34.47 mg/kg DM, and citrinin contents of 2.13-3.11 mg/kg DM. Among tested strains of molds, Monascussp. PSRU03 produced high monacolin K and lowest citrinin contents in noodle. Furthermore, this strain also produced the highest content of pigments. Therefore, this study suggested that Monascussp. PSRU03 has a potential for using as starter culture in the production process of noodle waste angkak.